Ownership structure and firm performance in Malaysia - Kamardin, Hasnah; Abdul Latif, Rohaida; Taufil Mohd, Kamarun Nisham (2016)
The aim of the study is to investigate the effect of different type of ownership structure on firm performance proxied by market measure (market to book value, MTBV) based on companies listed on Bursa Malaysia in the year 2006 to 2010. Firm performance in this study is proxied by market measure (market to book value, MTBV). Results of the study indicate that director ownership and foreign ownership have non-linear relationship with MTBV using quadratic function. While family ownership and ownership by government-linked investment companies have linear relationship. Director ownership has negative relationship which indicate the entrenchment effect at the lower stake.However, director ownership has positive relationship meaning the alignment effect occurs at the higher stake. However, foreign ownership has alignment effect at the lower stake and entrenchment effect at the higher stake. Government-linked investment companies has negative relationship.The findings of the study add to the ownership structure literature in the concentrated ownership market.